Epístolas do amor e da guerra: o espaço biográfico nas cartas de Olga Benário - Quillici, Mariana Bisaio (2015)
This dissertation presents the analysis of three letters, written by Olga Benario and addressed to Luiz Carlos Prestes, during the period when she was imprisoned in Nazi Germany of Adolf Hitler, and he in dictatorial Brazil of Getúlio Vargas. Understanding the importance of epistolary writing, especially when it becomes the only form of communication, we seek to find Olga profile brands that escape existing stereotypical view in the popular imagination. For this, we analyzed the letters from the perspective of war, love, and readings that Benario did, alongside his life, and records in the space of reflection that the letter provides. The proposal is to allow, through writing own Olga Benario, find his reflections, anguish and desires. Therefore, base us in theoretical as Alfredo Bosi, Leonor Arfuch, Maria Luiza Tucci Carneiro, Martin Gilbert, Peter Gay, Primo Levi, Silvina Rodrigues Lopes, Tzvetan Todorov, among others.